2013
DOI: 10.1042/bj20130205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evolution of protein–protein interaction networks

Abstract: The modern synthesis of evolutionary theory and genetics has enabled us to discover underlying molecular mechanisms of organismal evolution. We know that in order to maximize an organism's fitness in a particular environment, individual interactions among components of protein and nucleic acid networks need to be optimized by natural selection, or sometimes through random processes, as the organism responds to changes and/or challenges in the environment. Despite the significant role of molecular networks in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…Considering the important role of EF-Tu in the translational machinery, mutations accumulating directly on the EF-Tu gene can cause cell lethality and thus may not be readily adaptive (Goldman et al 2010; Kacar and Gaucher 2013; Pereira-Leal et al 2006). On the other hand, there are likely to be beneficial mutations that can occur without causing cell lethality, but they do not confer the advantage that others do under the same conditions, resulting in tuf mutations always being outcompeted within earlier generations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the important role of EF-Tu in the translational machinery, mutations accumulating directly on the EF-Tu gene can cause cell lethality and thus may not be readily adaptive (Goldman et al 2010; Kacar and Gaucher 2013; Pereira-Leal et al 2006). On the other hand, there are likely to be beneficial mutations that can occur without causing cell lethality, but they do not confer the advantage that others do under the same conditions, resulting in tuf mutations always being outcompeted within earlier generations.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical sequence reconstructions of ancient genes and their subsequent in vitro biochemical characterization alone, however, may not necessarily provide the salient details of why the protein evolved along a particular evolutionary pathway (Bar-Rogovsky et al 2015; Copley 2012; Dean and Thornton 2007; Kacar 2016; Zhu et al 2005). Incorporating a functional perspective into the study of ancient proteins was suggested to be instrumental for understanding historical adaptive pathways as well as bridging the evolution of protein-level function and the organism-level behavior, thus enabling predictions that connect inferred genotype to ancestral phenotype (Dean and Thornton 2007; Harms and Thornton 2013; Kacar and Gaucher 2013, 2012; Lunzer et al 2005; Zhu et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Nodes with a high node degree are called hubs, but a clear definition of what node degree should be regarded as “high” is missing [103]. Nevertheless, identifying nodes with a larger degree is a means for identifying essential proteins [104106], since the knockout of hub proteins most likely cause a substantial disruption in the interaction network [85]. We decided to classify proteins as essential when they are among the top 15 % proteins with respect to the node degree, a threshold commonly used [103].…”
Section: Methodsmentioning
confidence: 99%
“…Considering the important role of EF-Tu in the translational machinery, mutations accumulating directly on the EF-Tu gene can cause cell lethality and thus may not be readily adaptive (Goldman et al 2010;Kacar and Gaucher 2013;Pereira-Leal et al 2006). On the other hand, there are likely to be beneficial mutations that can occur without causing cell lethality, but they do not confer the advantage that others do under the same conditions, resulting in tuf mutations always being outcompeted within earlier generations.…”
Section: Discussionmentioning
confidence: 99%